Electronic properties of silicon surface at different oxide film conditions - Kirillova, S.I.; Primachenko, V.E.; Venger, E.F.; Chernobai, V.A. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2001)
We used measurements of temperature and electric field dependencies of surface photovoltage to study electronic properties of (100) n-silicon surface after its thermal and chemical oxidation, as well as after oxide films removal in HF. Measurements of surface photovoltage vs temperature curves revealed two peaks of the fast surface electron states (SES) density. They lie in the gap in the region of Pb₀₋ and Pb₁₋centers manifestation. The parameters of SES systems that were determined from the surface photovoltage vs electric field curves differ substantially from those determined from the temperature dependencies of surface photovoltage. They depend on the silicon surface condition, material resistivity and temperature at which the measurements were made. This is because the SES systems in oxide films (that exchange electrons with silicon via transport mechanisms) affect the measurements of electric field dependence of surface photovoltage.
Remove selected